Murder Dalam Pembelajaran Membaca Memahami Bahasa Jerman - Tahir, Imma; Jufri, Jufri; Achmad, Abdul Kasim (Interference: Journal of Language, Literature, and Linguistics, 2021)
The purpose of this study to obtain data and information about the effectiveness of the Murder type Cooperative Learning model in reading learning to understand German language for students of class XI MIPA SMAN 16 Makassar. The type of research is the Pre-Experimental Design (one group pretest postest design). The study population was the students of class XI MIPA SMA Negeri 16 Makassar which consisted of 1 class totaling 36 students. The sample of this study was selected using total sampling. Data were analyzed by t-test. The results of data analysis showed that the value of t count 2.40 â‰¥ t table 1.997 at a significant level of 0.05.Â  The results of this study indicate that the cooperative learning model of MURDER type in reading learning to understand German for Class XI MIPA SMA Negeri 16 Makassar is effective.Â